Epidemiological study of the associations between sleep complaints and metabolic syndrome in Japan. Issue 4 (18th June 2014) - Ikeda, Maki; Kaneita, Yoshitaka; Uchiyama, Makoto; Mishima, Kazuo; Uchimura, Naohisa; Nakaji, Shigeyuki; Akashiba, Tsuneto; Itani, Osamu; Aono, Hiroshi; Ohida, Takashi
Abstract The purpose of this study was to examine the associations of sleep complaints, such as insomnia and snoring, with metabolic syndrome. Data from a national study conducted on residents from randomly selected districts in Japan in 2007 were used. The survey included: (i) information on physical status, (ii) dietary intake, and (iii) a questionnaire on lifestyle characteristics. Data on physical status and lifestyle characteristics available for 3936 adults (1592 men and 2344 women) were analyzed. Multiple logistic regression analysis yielded statistically significant associations. Adjusted odds ratios calculated with reference to metabolic syndrome were 1.23 (95% CI: 1.03–1.48, P = 0.02) for insomnia and 1.89 (95% CI: 1.56–2.30, P < 0.01) for snoring. For insomnia, the adjusted odds ratio in relation to hypertension was 1.28 (95% CI: 1.08–1.52, P < 0.01), and for snoring, the adjusted odds ratios in relation to abdominal obesity and dyslipidemia were 1.90 (95% CI: 1.60–2.26, P < 0.01) and 1.50 (95% CI: 1.27–1.77, P < 0.01), respectively. Metabolic syndrome was found to be closely associated with insomnia and snoring. Such associations should be taken into consideration when developing measures against metabolic syndrome and sleep problems.